Emulating a Carbon Dioxide Trigger for the Fear Response - Frenger, Paul (CMBES Proceedings, 2010)
Breathing carbon dioxide can provoke the mammalian fear response, in particular the dread of smothering. This effect is mediated by pH changes which carbonic acid produces on acid sensing ion channels (ASIC) in the brain. Neurons in the amygdala are rich in ASIC type 1a receptors, making them effective low-pH hydrogen ion sensors. The amygdala are involved in producing high-level emotional responses and creation of longterm fear memories. Additionally, extracellular acidosis upsets membrane calcium ion activity, inhibits the sodium-potassium exchange pump, and makes zinc ions much more toxic to neurons. In this paper, the author extends his computerized human nervous system function emulation (HNSFE) technology to exhibit the effects of inhaled carbon dioxide on simulated ASIC receptors in the brain. These emulated effects include triggering of fear memories, epinephrine hormone release, hyperventilation, and fight-orflight behavior. The HNSFE, which imitates the brain’s biochemical-neural-cognitive operations, is a multitasking Forth language program which runs on an x86-based PC/104 multiprocessor network enhanced with 8-core 32-bit CPUs, analog circuits to support an artificial neural network and synthetic emotions, and cellular substrate-receptor binding activity simulations. ASIC function is imitated by a commercially-available CO2 sensor which is exposed to varying levels of carbon dioxide gas. This HNSFE - gas sensor ensemble produces emulated reactions which range from increased ASIC neural membrane activity through the fearful emotional response and finally to gross avoidant behavior.